Pengaruh Pola Konsumsi dan Pengelolaan Sampah terhadap Tingkat Kerusakan Lingkungan - Panggalih, Stella Ega (Maliki Interdisciplinary Journal, 2025)
Environmental degradation, which continues to increase each year, is a consequence of unsustainable consumption patterns and suboptimal waste management practices. This study aims to comprehensively examine how consumption behavior and waste management systems contribute to the level of environmental damage. Excessive consumption that disregards sustainability principles results in high volumes of waste. Meanwhile, poorly structured waste disposal practices by communities can lead to soil, water, and air pollution. Through a literature review of various studies and field practices, it was found that the implementation of community-based strategies such as the production of eco-enzymes, the utilization of waste into high-value products, and educational approaches through environmental programs can have a positive impact in reducing the rate of environmental degradation.